2019 Senior Thesis Project - Hagman, Kristina. (Tufts Archival Research Center, 2019)
Background: What have you touched today? What is your relationship with your body? These are only a few of the questions that occupy my mind. I believe that art has the power not only to publicize, but also to redeem some of the negative, objectionable, and destructive factors we encounter in our current world. Art has the power to inspire change.; Keywords: papermaking, books, mindfulness, breathing, narrative, poetry, touch, senses, painting.